Socio-pedagogical component of specialists’ training at the level of in-depth higher education - Afanasieva, Tatianna S.; Sidorova, Marina V. (University Pedagogical Journal, 2026)
The role and relevance of the socio-pedagogical component of training specialists in the field of education are substantiated. The purpose, objectives, and content of the academic disciplines in the specialty «scientific and pedagogical activity» (on the example of the academic disciplines «Socialisation and education in modern conditions» and «Cross-cultural communications»), which contribute to the formation of the socio-pedagogical competence of future specialists, are described. Based on the analysis of the results of the students’ survey, it is concluded that the socio-pedagogical component of training specialists plays an important role in the development of a teacher as a subject of their professional activity.
Keywords: social and pedagogical training; specialist competencies; advanced higher education; socialisation and upbringing; communication